ИНГЛИЗ ТИЛИДАГИ СЎЗ БИРИКМАЛАРИ ТАРКИБИЙ ҚИСМЛАРИНИНГ ЎЗАРО МУНОСАБАТИ (Scientific journal of the Fergana State University, 2023)
In  this article characteristic features of English phrases are defined; their forms, functions and use in the structure of the sentences are analyzed. Main attention to clarify the relationship between the components of the phrases is given.